A four-unit [c2]daisy chain connected by hydrogen bonds. Issue 83 (17th September 2015) - Zhang, Qian; Zhang, Chun-Hang; Yang, Jun-Hui; Xin, Peng-Yang; Xuan, Xiao-Peng; Wang, Jian-Ge; Ma, Na-Na; Guo, Hai-Ming; Qu, Gui-Rong
Abstract : A novel four-unit [c2]daisy chain without covalently-bound linear thread was constructed. Abstract : A mono-adenine-functionalized pillar[5]arene and a guest including uracil were prepared. They formed a novel four-unit [c2]daisy chain both in the solid state and in a chloroform solution. As far as we know, this [c2]daisy chain is the first one without a covalently bound linear thread. This unique assembly behavior is mainly induced by hydrogen-bond interactions between A and U in the A–U base pairs.